Migration histories of multidrug-resistant tuberculosis patients from the Thailand-Myanmar border, 2012-2014 - Thi, S; Parker, D; Swe, L; Pukrittayakamee, S; Ling, C; Amornpaisarnloet, K; Vincenti-Delmas, M; Nosten, F (International Union Against Tuberculosis and Lung Disease, 2017)
Multidrug-resistant tuberculosis (MDR-TB) is a growing public health threat in South-East Asia. TB is typically a disease of poverty and can be spread by infectious humans who migrate from one region to another. We interviewed 20 MDR-TB patients on the Thailand-Myanmar border with regard to their migration histories. Migration origins and destinations were mapped. All but one participant had a history of migration, and maps of migration ranges revealed wide geographic dispersal. Most described living and work conditions that could contribute to the spread of drug-resistant TB, including numerous contacts and crowded living quarters. Our results show that at least some migrant workers in the region carry MDR-TB, and indicate that this subgroup of the population is important with regard to the transmission of MDR-TB throughout the region. Migrants in this region come into contact with high numbers of people and may be able to spread the disease across wide geographic ranges. Access to diagnosis and treatment and socio-economic development are at least as important as any TB control measures, meaning that innovative and bold approaches that extend across international borders are needed to address these problems.